The Effect of Deep Learning Through Canva on English Achievement of SMA Class X Students - Marhamah Marhamah; Syofianis Ismail; Zetriuslita Zetriuslita; Sahid Agustian Hudjimartsu; Kurniawan Kurniawan; Dewanto Dewanto; Febri Abshor (Jurnal Ilmiah Profesi Pendidikan, 2026)
The lack of student interest in learning English significantly influences their learning outcomes. During the learning process, students greatly require media and learning approaches that can support their engagement and activeness in the classroom. The deep learning approach and Canva Magic AI media can serve as a potential solution to the problems faced by these students. This research aims to investigate the effect of deep learning aided by the Canva on the English achievement of Class X students at SMA IT Imam Syafi’i 2 Pekanbaru. The research method used is a quasi-experiment with a non-equivalent control group design. A total of classes was randomly selected, consisting of 40 students. One class served as receiving English learning integrated with deep learning and Canva, and the other as receiving conventional learning. The data collection instrument was an English achievement test administered before and after the treatment. The collected data were analyzed using inferential statistical tests to compare the improvement in learning achievement between the two groups. The results of this study are expected to provide the effectiveness of combining deep learning and Canva in improving the English learning outcomes of SMA students, as well as its implications for innovation in language teaching practices.